Strengthening the Knowledge and Skills of Healthcare Workers in Detecting and Referring Cases of Sexual Violence at Karang Anyar Community Health Center (JURNAL PENGMAS KESTRA (JPK), 2025)
Sexual violence against women and children is a serious issue that affects both physical and long-term psychological health. National data indicate that one in four women aged 15–64 years has experienced physical or sexual violence, while more than half of children report having experienced various forms of violence. Healthcare workers in primary care facilities, such as community health centers (Puskesmas), play a strategic role in managing these cases as they often serve as the first point of contact for victims. However, limited knowledge and skills among healthcare workers often hinder early detection and proper referral of cases. This Community Service Program (PkM) aimed to enhance the knowledge and skills of 25 healthcare workers at Puskesmas Karang Anyar in detecting and referring cases of sexual violence against women and children. The program was designed using an interactive training approach, including lectures, group discussions, case studies, and referral simulation exercises. Pre-tests and post-tests were administered to measure participant competency improvements, supported by observations of simulation practices. The results demonstrated significant improvements across all evaluated aspects. The average participant score increased from 50.2 to 82.9, with an overall improvement of 64.9%. Detection skills of signs and symptoms of violence increased by 69.4%, sensitive communication skills by 64.5%, and understanding of referral procedures by 63.8%. These findings confirm that interactive educational methods effectively enhance practical abilities, procedural understanding, and psychological readiness of healthcare workers. Overall, this PkM significantly improved healthcare worker competency, preparing them to handle sexual violence cases ethically, sensitively, and according to integrated healthcare standards.